Kemampuan Constructed Wetland Jenis Aliran Bawah Permukaan (SSF - Wetland) Dalam Mengolah Air Limbah Kawasan Komersial - Oni Loretha; Lita Darmayanti; Yohanna Lilis Handayani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Wastewater of commercial areas such as hotels, shops, restaurants, offices, and shopping centers relatively contain high pollutant concentrations, they caused the imbalance of drainage ecological quality, health problems, and the water pollution itself. The effective technology in treating waste wateris The Sub Surface Flow Constructed Wetland (SSF-Wetland) that maximize either the impact or the potentcy of the plants in treating waste waterin the physical, chemical and biological wayby using plants/vegetation, water and microorganisms to reduce the level of pH, Chemical Oxygen Demand (COD), and the level of Total Suspended Solid (TSS) contained in waste water by slowly flowing them through the inlet hole to the surface covered by the living plants. The experimental result shows by using bamboo water plant (Equisetum hyemale) in artificial wetland system, the content of pollutants in wastewater can be eliminated. The highest average value of COD reduction efficiency is 61.9 %, 92.6 % of TSS and the decreasing of pH reaches 29.4%. The advantage of wastewater treatment using this system enables us to produce the appropriate water quality of the domestic wastewater based on the quality standards.  Keywords:Equisetum hyemale, SSF-Wetland, wastewater